Editors’ Word - Ejdus, Filip; Džuverović Nemanja; Kovačević, Marko; Vujinović, Nikola (Journal of Regional Security, 2018)
The Journal of Regional Security has a great pleasure to welcome Nemanja Džuverović (University of Belgrade, Faculty of Political Sciences) as new co-editor and Roger Mac Ginty (The University of Manchester) and Petra Roter (University of Ljubljana) as new members of the Editorial Board. The Journal also developped a brand new website – www.regionalsecurityjournal.com. All back issues are in a Gold Open Access regime and available for free download. We invite you to visit our website, browse our archives and provide us with your valuable feedback. In the following period the Journal will focus on the topics such as Regional Security Complex Theory, memory/security nexus and civilian capacities for participation in peace support operations. We invite all potential authors to send us their manuscripts on these or other issues relevant for our subject matter.